Some theoretical questions of studying the development of conceptual thinking - Garbačiauskienė , M. (Psichologija, 1980)
In this article, comparing J. Piaget and L. Vygotsky's directions in the studies of the development of thinking, the results obtained and difficulties arisen, the studies of other authors in this field, we try to ground the principle of two substructures in conceptual thinking - the substructure of signals and the substructure of symbols. The development of their integrated and differentiated activity marks the development of conceptual thinking.
Keywords: J. Piaget; L. Vygotsky; conceptual thinking